Enhancement of photocatalytic efficiency using heterostructured SiO2–Ta2O5 thin films. (27th May 2015) - Baruah, Arabinda; Jha, Menaka; Kumar, Santosh; Ganguli, Ashok Kumar
Abstract: Fabrication of controlled layered structured thin films with tunable physical properties is an important area of research as thin film technology holds potential for a variety of industrial applications. In the present work, we have demonstrated the process for fabrication of multilayer films of silica and tantalum oxide by Langmuir–Blodgett film fabrication technique and investigated their photocatalytic degradation efficiency for organic dye (Rhodamine B) under UV radiation. The photocatalytic degradation of RhB in presence of SiO2 –Ta2 O5 exhibited remarkably enhanced photocatalytic activity than pure Ta2 O5 . This is because of the high separation efficiency of photo-generated electron–hole pair due to the Lewis acidity of silica and the greater contact area between these two layers. The SiO2 –Ta2 O5 system was optimized for the number of self-assembled layers of silica and tantalum oxide, and it has been found that 10S–15T–10S–15T–10S–15T (where S and T represents SiO2 and Ta2 O5 respectively) pattern has been found to have maximum photocatalytic degradation efficiency of 71% (with 18% degradation per unit area of the film) which is 3.5 fold higher than pure Ta2 O5 under identical experimental condition. Also, the photocatalytic activity of these films was also proved to be sensitive to the sequence of silica and tantalum oxide layers when the film area of all the samples was kept constant (3.75 cm 2 ). Further analysis confirms that the degradation of dye molecules has been largely promoted by the photo generated holes, rather than the super oxide radical anions.